Posterolateral Endoscopic Thoracic Discectomy: Transforaminal Approach - Sang Ho Lee (Neurologico Spinale Medico Chirurgico, 2018)
Objective: Symptomatic soft herniated thoracic disc (HTD) before the use of magnetic resonance imaging (MRI) was a rare disease with less than 1% of all spinal disc herniation. The frequency of diagnosis of thoracic disk herniation has increased with the routine use of MRI. To avoid high morbidity and complications associated with conventional approach, the authors applied posterolateral endoscopic technique. Methods: From January 2001 to December 2016, 87 patients with non-sequestrated and soft lateral or central thoracic disc herniation underwent posterolateral endoscopic thoracic discectomy (PLETD). Under local anaesthesia with intravenous sedation, we removed the herniated disc through thoracic intervertebral foramen after foraminoplasty. The enlargement of the foramen by partially cutting the lateral aspect of superior facet with a Reamer or high-speed diamond drills. Clinical outcome was measured by the Oswestry Disability Index (ODI) and the visual analogue scale. Results: Fifty-one males and thirty-six females, aged 21 to 89 years were enrolled in this study. Mean follow-up period was 10 months (1 to 56 months). The mean ODI scores improved from 53.7 before surgery to 16.9 at the final follow-up (p < 0.05). Mean VAS scores improved from 7.3 before surgery to 2.1 at the final follow-up (p < 0.05). One patient required conversion to an open procedure for recurred disc protrusion in 17 days. Another one patient required repeated PLETD for recurring disc in l year. Three patients experienced transient low extremity paresthesia but all improved. There were no other serious complications associated with this procedure. Conclusion: Conventional treatment of HTD is known for its high morbidity and complications, posing a challenge to physicians. This PLETD technique for symptomatic non-sequestrated and soft HTD is a safe and effective method that provides a direct route to the lesion under local anaesthesia with less morbidity.